Implementation of Article 3 Paragraph (2) PM 33 of 2015 Concerning Perimeter Requirements at Abdulrachman Saleh Airport Malang - Ghifari Syahara Ramadhan; Sri Sutarwati (CV. Rayyan Dwi Bharata, 2023)
Perimeter requirements regulations for domestic airports have been regulated in Article 3 Paragraph (2) PM 33 of 2015. Abdulrachman Saleh Malang Airport as a domestic airport must meet the perimeter requirements stipulated in the minister of transportation regulation. This study aims to find out how the Implementation of Article 3 Paragraph (2) PM 33 of 2015 regarding perimeter requirements at Abdulrachman Saleh Airport Malang. This study uses primary data and secondary data. The subjects in this study were Aviation Security officers. Data collection methods used are observation, interviews, and documentation. The location of this research was carried out at the East Java Transportation Service UPT for placement in the Aviation Security (Avsec) and Apron Movement Control (AMC) sections. Data analysis used descriptive qualitative. The research results obtained show that Abdulrachman Saleh Malang Airport has implemented most of the perimeter requirements that have been stipulated in Article 3 Paragraph (2) PM 33 of 2015 such as the perimeter fence is mostly 2.44 meters high, provision of trellis on drainage, available visibility around the barrier, inspection roads are available and equipped with emergency exits. The perimeter requirements that have not been met at Abdulrachman Saleh Airport are that there are still found a perimeter that is less than 2.44 meters high, there are gaps that can be easily penetrated by people and wild animals and there are no lights around the perimeter fence.